Hydronephrosis in Children Caused by Lower Pole Crossing Vessels—How to Choose the Proper Method of Treatment? - Polok, Marcin; Toczewski, Krystian; Borselle, Dominika; Apoznański, Wojciech; Jędrzejuk, Diana; Patkowski, Dariusz (Frontiers in Pediatrics, 2019)
Aim: Assessment of the efficacy of intraoperative diagnosis between extrinsic and intrinsic UPJO in children. Assessment of the efficacy of laparoscopic vascular-hitch procedure in UPJO caused by lower pole crossing vessels (CV). Material and methods: Between 2008 and 2017, 47 laparoscopic procedures were performed with the CV discovered intraoperatively. CV were translocated cephalad, and the UPJ was carefully inspected. The Chapman’s vascular hitch procedure was accomplished in the case of decreasing sizes of the pelvis and clear, visible peristalsis of the UPJ (31 patients). In the other cases, Anderson–Hynes (A-H) pyeloplasty with posterior translocation of the CV was performed (16 patients). Results: The median age at operation was 6 years (range 1-16) in VH and 6 years (range 2-17) in A-H (p=0.4635). Prenatal dilatation of kidney was diagnosed in 18.7% of VH and 10% of A-H cases (p=0.5474). Success was achieved in 16 (100%) patients in the A-H and in 29 (93.54%) in the VH groups. Two patients (6.5%) in VH required repeated surgery because of a misdiagnosed intrinsic obstruction. Median operation time in VH was 80 minutes (range 40-105) and was 105 (range 70-225) in A-H (p<0,05). Conclusions: The intraoperative selection based on intraoperative pelvis and UPJ appearance after vessel transposition is sufficient in majority of cases. Laparoscopic vascular hitch seems to be effective and safe procedure, but can only be performed on carefully selected patients. In case of misdiagnosis, reoperation is possible with the same laparoscopic access.